The origin of the domestic animals of Africa - Epstein, H. (Africana Publishing Corporation, 1971)
The monograph presents studies of over forty years of research on the origin and development of domestic animals of Africa. It discusses the dog, cattle and buffalo of Africa. Each chapter opens with a survey of the wild species from which the domestic may have descended, followed by extensive descriptions of the morphological, physiological, taxonomic and distribution characteristics of the African breeds and varieties of the animal. The historical and prehistorical records are traced back to the animal's place of origin in Asia, Europe, or Africa; to establish the relationship of the domestic species to the wild species and to extinct archaeologically established form and vis-a-vis.